Transcriptomic leaf profiling reveals differential responses of the two most traded coffee species to elevated [co2] - Marques, Isabel (2020)
PTDC/ASP-AGR/31257/2017 UIDB/00239/2020 UIDP/04035/2020 UID/AGR/04129/2020 UIDB/04551/2020 CRA-RED-00053-16